2011
DOI: 10.1007/s11199-011-9933-4
|View full text |Cite
|
Sign up to set email alerts
|

Self- and Partner-objectification in Romantic Relationships: Associations with Media Consumption and Relationship Satisfaction

Abstract: Few studies have examined objectification in the context of romantic relationships, even though strong theoretical arguments have often made this connection. This study addresses this gap in the literature by examining whether exposure to mass media is related to self-objectification and objectification of one’s partner, which in turn is hypothesized to be related to relationship and sexual satisfaction. A sample of undergraduate students (91 women and 68 men) enrolled in a university on the west coast of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

17
167
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 108 publications
(184 citation statements)
references
References 58 publications
(94 reference statements)
17
167
0
Order By: Relevance
“…What self-objectification appears to do is help make the system more palatable for women (Jost, 1995), especially under conditions of greater epistemic (Calogero & Jost, 2011), existential (Goldenberg et al, 2011), and relational (Zurbriggen, Ramsey, & Jaworski, 2011) Running head: OBJECTS AND ACTIONS 23 stress. Investment in appearance as the means to self-worth and social status brings the self in line with the system, which motivates women to work harder in the service of that system.…”
Section: Demonstrated That Appearancementioning
confidence: 99%
“…What self-objectification appears to do is help make the system more palatable for women (Jost, 1995), especially under conditions of greater epistemic (Calogero & Jost, 2011), existential (Goldenberg et al, 2011), and relational (Zurbriggen, Ramsey, & Jaworski, 2011) Running head: OBJECTS AND ACTIONS 23 stress. Investment in appearance as the means to self-worth and social status brings the self in line with the system, which motivates women to work harder in the service of that system.…”
Section: Demonstrated That Appearancementioning
confidence: 99%
“…Indeed, in a sample of college students, Zurbriggen, Ramsey, and Jaworski (2011) found that objectifying one's partner was associated with lowered relationship satisfaction, for both men and women. If objectification leads to dehumanization and its corresponding negative consequences, it seems quite likely that feeling objectified (as opposed to doing the objectification, as was assessed in Zurbriggen et al, 2011) would also relate to lowered relationship satisfaction. The present research examines partner-objectification in relationships from the perspective of the person feeling objectified (termed ''perceived partner-objectification''), and it is the first known study to directly test the hypothesis that perceived partner-objectification is related to lowered relationship satisfaction.…”
Section: Introductionmentioning
confidence: 99%
“…Self-objectification has consequences such as continual body and appearance monitoring and requires cognitive attention that can interfere with task performance. According to the theory being objectified by others is thought to precede self-objectification; hence objectification by others (i.e., other-objectification) may be even more widespread and perhaps more insidious, than self-objectification (Zurbriggen et al, 2011). Furthermore, Strelan and Hargreaves (2005) found that women were less likely to objectify themselves (self-objectification), than to objectify other women (other-objectification).…”
Section: Objectification Theorymentioning
confidence: 99%
“…As compared to participants who saw videos of female artists low in SO, those who saw videos of female artists high in SO reported more adversarial sexual beliefs and were more accepting of interpersonal violence. Zurbriggen et al (2011) surveyed undergraduate men and women to study whether consumption of mass media (i.e., TV, films, magazines) was associated with other-objectification in the context of romantic relationships. They found that consumption of mass media was positively related to partner objectification (other-objectification), which was negatively related to relationship satisfaction.…”
Section: Objectification Theorymentioning
confidence: 99%
See 1 more Smart Citation